Nutritional health services for pregnant women: A qualitative study - Rena Herlina; Rukmaini Rukmaini; Lisa Trina Arlym (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Nutritional health services play a crucial role for pregnant women in supporting fetal growth, preventing complications, and reducing the risk of stunting. Purpose: To explore nutritional health services for pregnant women. Method: A phenomenological approach involving 11 informants (pregnant women, family members, healthcare workers, community cares, and policymakers). Data were collected through in-depth interviews and analyzed using thematic analysis to identify patterns and themes emerging from participants’ narratives. Results: The analysis generated 47 codes, which were grouped into 8 categories and distilled into two main themes: (1) Experiences of Receiving Nutritional Services, including routine screening, internal referrals, multidisciplinary collaboration, availability of supplements/PMT, and digital media–based education; (2) Barriers in Nutritional Practices and Uptake, including brief communication due to workload, low effectiveness of conventional education, internal constraints (nausea, side effects, forgetting to take supplements), socio-economic challenges, conflicts between medical advice and family traditions, as well as perceptions that services are more beneficial for high risk patients. Conclusion: Although nutritional services are relatively well-structured and adequate, their implementation still faces significant barriers related to communication, education, internal, socio economic, and cultural factors. These findings highlight the need for interventions focusing on more effective communication strategies and strengthening the role of reliable information sources to improve the nutritional status of pregnant women.